Job Stress and Job Involvement: The Direct Role of Perceived Coworker Support - Astuti, Reni Puji; Kurniawan, Ignatius Soni; Kusuma, Nala Tri (Journal of Management Studies and Development, 2025)
This study examines the relationship between job stress and job involvement, and evaluates the direct role of perceived coworker support within an educational foundation setting. Using a quantitative survey involving all 75 employees of the Mahaduna Rohmatul Umam Foundation, data were analyzed using PLS-SEM. The results indicate that job stress does not significantly influence job involvement. Meanwhile, perceived coworker support demonstrates a strong and significant direct effect on job involvement, although it does not moderate the relationship between job stress and job involvement. These findings suggest that supportive colleagues can sustain employee involvement even when job stress is present. The study partially supports the Job Demands- Resources Model by highlighting the importance of job resources, particularly social support, in maintaining involvement. Practically, organizations are encouraged to foster collaboration and open communication to strengthen employees’ job involvement.